2021
DOI: 10.1186/s10020-021-00268-5
|View full text |Cite
|
Sign up to set email alerts
|

Exosomal miR-335 derived from mature dendritic cells enhanced mesenchymal stem cell-mediated bone regeneration of bone defects in athymic rats

Abstract: Background Transplantation of bone marrow-derived mesenchymal stem cells (BM-MSCs) embedded in a bio-compatible matrix has been demonstrated as a promising strategy for the treatment of bone defects. This study was designed to explore the effect and mechanism of exosomes derived from mature dendritic cells (mDC-Exo) on the BM-MSCs-mediated bone regeneration using the matrix support in an athymic rat model of femoral bone defect. Methods The BM-MSCs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 30 publications
0
19
0
Order By: Relevance
“…Because of the signals and nutrients delivered by exosomes, macrophages are broadly involved in a number of physiological processes and pathological diseases such as cancer [ 18 ], inflammation [ 19 ] and tissue repair [ 20 ]. In addition, macrophages exosomes also participate in bone remodeling [ 21 ]. However, the exosomes derived from different types of macrophages have been shown to exert different functional effects on osteogenesis [ 22 , 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…Because of the signals and nutrients delivered by exosomes, macrophages are broadly involved in a number of physiological processes and pathological diseases such as cancer [ 18 ], inflammation [ 19 ] and tissue repair [ 20 ]. In addition, macrophages exosomes also participate in bone remodeling [ 21 ]. However, the exosomes derived from different types of macrophages have been shown to exert different functional effects on osteogenesis [ 22 , 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have found that exosomes play a vital role in bone diseases ( 15 , 16 ). In a rat calvarial defect model, macrophage exosomes could mediate bone regeneration ( 17 ). However, it has also been reported that exosomes from M0, M1, and M2 macrophages might have different effects on the osteogenic differentiation of BMSCs ( 18 , 19 ).…”
Section: Introductionmentioning
confidence: 99%
“…For example, the RNA-sequencing of osteogenic exosomes from human MSCs suggests that exosomes include upregulated osteogenic miRNAs (Hsa-miR-146a-5p, Hsa-miR-503-5p, Hsa-miR-483-3p, and Hsa-miR-129-5p) or downregulated anti-osteogenic miRNAs (Hsa-miR-32-5p, Hsa-miR-133a-3p, and Hsa-miR-204-5p), which activate the PI3K/Akt and MAPK signaling pathways ( Zhai et al, 2020 ). In addition, MSC-released exosomal miR-1260a ( Wu et al, 2021 ); miR-335 ( Cao et al, 2021 ); miR-140 and miR-375 ( Chen et al, 2019 ); miR-26a, miR-199a, miR-21, and miR-23a-3p ( Hu et al, 2020 ); let-7a-5p, let-7c-5p, miR-328a-5p, and miR-31a-5p ( Liu A. et al, 2021 ); and miR-150-5p ( Jing et al, 2022 ) have been reported to promote osteogenesis. The exosomes promoting osteogenesis involve many pathways, such as BMP/Smad, Wnt/β-catenin, PTEN/PI3K/Akt, and Hippo signaling pathways ( Cao et al, 2021 ; Cui et al, 2016 ; Hu et al, 2020 ; Zhang et al, 2016 ).…”
Section: Applications Of Bone Engineering Scaffolds With Exosomes In ...mentioning
confidence: 99%